Alleviating effect of different configuration tartaric acids on aluminum toxicity in barley seedlings - GUO Tian-rong; GU Qun-yan; HU Li-yan; SHENG Yan-jun (浙江大学学报. 农业与生命科学版)
The nutrient solution experiment was undertaken to assess the aluminum toxicity and the difference of different configuration tartaric acids in alleviating Al toxicity in barley seedlings. Al stress treatments adversely inhibited plant growth and photosynthesis, increased MDA content and activities of SOD and POD in barley seedling leaves. The differences between Al stress and the control increased with increasing Al level in solution. Plant growth and photosynthesis were obviously improved, and MDA content and activities of SOD and POD were reduced when adding 1.0 mmol·L-1 L-tartaric acid into the solution with Al treatment. There was no significant change in all examined indexes with 1.0 mmol·L-1 D-tartaric acid addition, compared with the single Al treatment. Thus, it can be concluded that alleviation of Al toxicity in barley seedlings by tartaric acid is dependent on its chemical structure.